2020
DOI: 10.17507/jltr.1101.12
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of Saudi Admission Criteria for Freshmen Students’ English Performance: Experience of King Saud Bin Abdulaziz University for Health Sciences

Abstract: This study examines the relationship and correlation between initial admission criteria and  English performance of first year students at King Saud bin Abdulaziz University for Health Sciences. The performance of 1,595 English language students was compared to the initial academic admission criteria to determine if a correlation exists between academic achievement pre and post admission.  Admission criteria include high school grades, General Aptitude Test score (GAT), and Scholastic Achievement Admission Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…only the total scores) and university GPA of different majors. Similarly, the study confirms Althewini and Alkushi's (2020) study where they examined the GAT's prediction of English performance for Health-majored students. The prediction of the test means the higher a student scores in the test, the higher the score will be in the English language tests and course grades.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…only the total scores) and university GPA of different majors. Similarly, the study confirms Althewini and Alkushi's (2020) study where they examined the GAT's prediction of English performance for Health-majored students. The prediction of the test means the higher a student scores in the test, the higher the score will be in the English language tests and course grades.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, Alanazi (2014) found that the GAT score can be a strong predictor for each of its two sections, the numerical and verbal or as a total score, regardless of student's major in high school, and that the GAT score explains 13.2% of variances in first semester's GPA. Althewini and Alkushi (2020) examined the relationship between the GAT's sections' scores and performance of English for students majoring in Health Sciences at a Saudi university. They found that the GAT along with other two academic criteria predicted cumulatively 17.3% of performance in English for this population of students.…”
Section: The General Aptitude Testmentioning
confidence: 99%
“…However, SAAT had a significant relationship with GPA in those studies. In one university, an increase in SAAT weightage has already been implemented [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…HSP and SAAT had a significant correlation with early academic performance, while GAT did not. An article [ 8 ] explores the relationship of HSP, SAAT and GAT with English performance for first-year students at King Saud Bin Abdulaziz University for Health Sciences. It identified that GAT had higher significance than SAAT in predicting English performance, while HSP had no significance.…”
Section: Introductionmentioning
confidence: 99%